Return to work after spinal cord injury: factors related to time to first job - Ramakrishnan, K.; Mazlan, M.; Julia, P.E.; Latif, L.A. (2011)
Study design: Cross-sectional survey. Objectives: To investigate factors related to length of time between spinal cord injury (SCI) onset and start of first post-injury employment. Setting: Persons living with SCI in the community who are members of a disability support organization. Methods: Participants were randomly selected from the membership list of a non-governmental voluntary organization. They met the following four criteria: traumatic SCI, minimum of 15 years of age at the time of survey, a minimum of 2 years after SCI and had been employed for some time since SCI. The main outcome measure was time (in years) from injury onset to beginning first post-injury job. Results: Participants averaged 4.9 years (s.d. 5.1) from the time of SCI to their first post-injury job, with a range of 3 months to 20 years. Fifty percent of the participants who eventually returned to work had done so by 4 years. Return to pre-injury employer and employment were associated with early return, whereas having less years in education and being older at the time of injury were associated with longer time to return to work. Conclusion: Rehabilitation team need to consider return to employment as a realistic goal even many years after SCI. Perhaps a focus on returning more people to their pre-injury employer and employment with added focus and input from rehabilitation team for those with lower education status and older age at time of injury might expedite the process of reintegration. Spinal Cord (2011) 49, 924-927; doi:10.1038/sc.2011.16; published online 8 March 2011